PELATIHAN KEWIRAUSAHAAN BAGI PEMULA DI DESA KRUCIL: MENINGKATKAN KEMANDIRIAN EKONOMI MASYARAKAT - M. Nabat Ardli; Reza Hilmy Luayyin (DEVELOPMENT: Journal of Community Engagement, 2024)
The entrepreneurship training program for beginners in Krucil Village, Probolinggo Regency, was designed to enhance the community’s understanding of entrepreneurship concepts while encouraging them to start new businesses. This training employed the Participatory Action Research (PAR) approach, actively involving the community in every stage of the program. Evaluation results showed a significant improvement in participants' understanding, increasing from 20% before the training to 85% afterward. Additionally, within a month after the training, 40% of participants successfully started new businesses, with snack production (35%) and handicrafts (25%) being the most chosen business sectors. Participants who started businesses reported an average income increase of 20%. The training also motivated participants to actively seek other business opportunities, focusing on utilizing local potential such as agricultural products and natural village resources. However, to ensure the program's long-term impact, further efforts are needed, including business mentoring, access to financing, and more specific advanced training tailored to the participants' business needs. With an integrated and sustainable approach, the Krucil Village community is expected to achieve greater economic independence and optimize local potential sustainably. This success also serves as an inspiration for developing economic empowerment programs in other villages with similar characteristics.